Dokumen Kontrak : maintenance works on low voltage electrical services in Universiti Teknologi Malaysia Skudai Johor - Universiti Teknologi Malaysia; Zulaz Engineering Sdn. Bhd (Skudai : Universiti Teknologi Malaysia, 2004)
15